HISTORY AS A TOOL FOR SHAPING HISTORY: THE EXAMPLE OF FEMI OSOFISANâ€™S WOMEN OF OWU - Adedeji, Niyi (European Scientific Journal, ESJ, 2015)
The use of history as a robust resource material in the African literary creativity is as old as the advent of modern African literature itself. This trend re-affirms the inevitability of the convergence of history and literature. In the symbiotic relationship, history feeds literature with factual events of the past the same way literature brings fullness to bear on such facts. Be this as it may, it is viewed that the use to which history is put by literature has taken diverse shades under different literary phases and/or canons. While we have writers, predominantly within the foremost African literary coterie, whose employment of history revels in the conventional historiography of â€œrender it and leave it at thatâ€, we also have writers (predominantly in the emergent radical canon) who employ the resource of history basically for the purpose of its dialectical dissection. In this connection, this paper seeks to investigate the radical use to which history is being put by writers of the latter canon. Femi Osofisanâ€™s Women of Owu shall be our representative literary piece. The thrust is to unravel how the text has employed the instrumentality of the historical resource of the war in the ancient Yoruba Kingdom of Owu to vehicle its revolutionary message.